2017
DOI: 10.1016/j.kint.2016.12.010
|View full text |Cite
|
Sign up to set email alerts
|

The renal TRPV4 channel is essential for adaptation to increased dietary potassium

Abstract: To maintain potassium homeostasis, kidneys exert flow-dependent potassium secretion to facilitate kaliuresis in response to elevated dietary potassium intake. This process involves stimulation of calcium-activated large conductance maxi-K (BK) channels in the distal nephron, namely the connecting tubule and the collecting duct. Recent evidence suggests that the TRPV4 channel is a critical determinant of flow-dependent intracellular calcium elevations in these segments of the renal tubule. Here, we demonstrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
47
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 58 publications
4
47
1
Order By: Relevance
“…1 and 3) in primary cultured human kidney cells that are of predominantly distal tubule origin (35). We found that TRPV4 function was identical to that reported in freshly isolated distal tubules of mice and rats (10,28,29), which points to a high level of conservation of molecular determinants conferring mechanosensitivity to renal tubule cells between rodents and humans. Considering that the kidney exhibits the highest level of TRPV4 expression compared with other tissues and organs (26), targeting channel activity could be a relatively specific strategy by which to regulate [Ca 2+ ] i signaling in renal epithelial cells.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…1 and 3) in primary cultured human kidney cells that are of predominantly distal tubule origin (35). We found that TRPV4 function was identical to that reported in freshly isolated distal tubules of mice and rats (10,28,29), which points to a high level of conservation of molecular determinants conferring mechanosensitivity to renal tubule cells between rodents and humans. Considering that the kidney exhibits the highest level of TRPV4 expression compared with other tissues and organs (26), targeting channel activity could be a relatively specific strategy by which to regulate [Ca 2+ ] i signaling in renal epithelial cells.…”
Section: Discussionsupporting
confidence: 78%
“…Whereas TRPV4 can be detected in many epithelial tissues, including lung, spleen, skin, sweat glands, as well as in other organs (23)(24)(25)(26)(27), expression of the channel is much higher in the kidney (26). We have previously demonstrated that TRPV4 is essential for mediating flowdependent [Ca 2+ ] i elevations in the connecting tubule and CD (28)(29)(30). Furthermore, it was reported that TRPV4 predominantly exists as a heterotetramer with PC2 in a 2:2 presumable stoichiometry (31) that forms a 23-pS Ca 2+ -permeable channel at the apical membrane of CD cells (32,33).…”
mentioning
confidence: 99%
“…Recently, it has been demonstrated that both aldosterone and high K + diets increase the total expression of TRPV4 in primary and immortalized mouse CCD cells [ 84 ]. It was notable that TRPV4 expression in mice treated with MR antagonists was below control, implying that aldosterone constitutively regulates TRPV4 [ 84 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been demonstrated that both aldosterone and high K + diets increase the total expression of TRPV4 in primary and immortalized mouse CCD cells [ 84 ]. It was notable that TRPV4 expression in mice treated with MR antagonists was below control, implying that aldosterone constitutively regulates TRPV4 [ 84 ]. This study further demonstrated that high K + diets, which should induce aldosterone release [ 85 ], increased TRPV4 apical membrane expression and increased flow-mediated [Ca 2+ ] i [ 84 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation